Association of coronary atherosclerosis with hyperapobetalipoproteinemia [increased protein but normal cholesterol levels in human plasma low density (beta) lipoproteins]. - Sniderman, A (1980)
Most patients with coronary artery disease do not have elevated plasma or low density lipoprotein (LDL) cholesterol. To test whether the protein moiety of LDL, LDL B, might be a parameter to identify ischemic heart disease, the plasma cholesterol, triglyceride, LDL cholesterol, and LDL B were measured in 100 consecutive patients undergoing cardiac catheterization. On the basis of coronary angiography, these patients were divided into two groups: group I, 31 patients without, and group II, 59 patients with significant coronary artery disease. Although cholesterol, triglyceride, and LDL cholesterol levels were all significantly higher in group II, discriminant analysis indicated that LDL B concentrations most clearly separated the two groups. In group I (noncoronary), LDL B was 82 +/- 22 mg/100 ml, whereas in group II, LDL B was 118 +/- 22 mg/100 ml. The B protein level in group I was similar to other normal groups studied (35 asymptomatic male physicians, 83 +/- 11 mg/100 ml; 90 normolipidemic medical students, 72 +/- 17 mg/100 ml). The results therefore indicate that not only does LDL B better separate coronary and noncoronary groups than other lipid parameters studied, but also, among those with coronary artery disease, there exists a group with normal LDL cholesterol but with levels of LDL B protein similar to those observed in type II hyperlipoproteinemia. The explanation for the altered LDL composition observed in this group remains to be elucidated.